2005
DOI: 10.1080/10520290500387847
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin immunohistochemistry of gastric adenocarcinoma and mucoepidermoid carcinoma of salivary gland

Abstract: Ghrelin (G-HH) synthesized in several tissues including salivary and stomach glands stimulates appetite in humans by modulating neuropeptide Y neurons in the hypothalamic arcuate nucleus. Loss of appetite is one of the most important symptoms of stomach cancer. We conducted a study using immunohistochemistry to determine whether salivary glands and stomach cancer tissues produce ghrelin. We determined that negative ghrelin immunohistochemistry discriminates tumors from normal tissues and may therefore further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…In IHC reaction for obestatin of salivary gland in present study, however, ıt was exhibited that the duct in a human salivary gland bears obestatin. These observation are supported by the fact that some other salivary proteins (including ghrelin) have been demonstrated to be yielded in the striated ducts of human salivary gland (20,21). Another supporting evidence that portions of some of these striated duct protein relased basally into circulation (20).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In IHC reaction for obestatin of salivary gland in present study, however, ıt was exhibited that the duct in a human salivary gland bears obestatin. These observation are supported by the fact that some other salivary proteins (including ghrelin) have been demonstrated to be yielded in the striated ducts of human salivary gland (20,21). Another supporting evidence that portions of some of these striated duct protein relased basally into circulation (20).…”
Section: Discussionmentioning
confidence: 84%
“…These observation are supported by the fact that some other salivary proteins (including ghrelin) have been demonstrated to be yielded in the striated ducts of human salivary gland (20,21). Another supporting evidence that portions of some of these striated duct protein relased basally into circulation (20). Here we can not rule out the possibility of basal secretion of obestatin, since we do not have evidence of mRNA for obestatin in human salivary glands, but Gröschl and his co-workers have demonstrated ghrelin mRNA expression in the 3 majors' salivary glands (sublingual and submandibular gland, parotid) as well as in oral keratinocytes (22).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, controversial evidence exists. Some studies reported that ghrelin was not detected in human somatotroph adenomas (Wasko et al, 2006), mucoepidermoid carcinoma of salivary gland (Aydin et al, 2005), esophageal (Mottershead et al, 2007) and gastric (Aydin et al, 2005;Mottershead et al, 2007) adenocarcinoma, and gastrointestinal endocrine tumors with multiple endocrine neoplasia type 1 (Raffel et al, 2005). The authors indicated that an infiltrating adenocarcinoma could decrease ghrelin production and disrupt local paracrine mechanisms by replacing normal gastric mucosa (Mottershead et al, 2007).…”
Section: B Anorexia and Cachexiamentioning
confidence: 99%
“…Regarding the possible use of ghrelin as a tumor marker, some tumors expressing ghrelin show increased ghrelin levels compared with normal tissue (e.g., breast, colorectal adenocarcinoma, and esophageal SCC), whereas others show decreased levels (e.g., endometrial carcinomas, renal cancer, and salivary gland mucoepidermoid cancer). 17,[30][31][32][33][34][35] The ghrelin expression patterns of various tumors have shown heterogeneous results, and the overor underexpression of biomarkers compared with healthy tissue added predictive value over microscopic evaluation. 14 The differences in ghrelin expression in different tumors may be related to tissue differences and their embryological origins.…”
Section: Fig 2cmentioning
confidence: 99%